Intraocular Gnathostoma spinigerum: a case report - Tiwari, Shreekant (BioMed Central, 2009)
Live intraocular nematode is a rare occurrence that is mostly reported in South East Asian countries. Herewith we report such a case from Nayagarh district of Odisha. A 28 year old female presented with swelling, redness, lacrimation, pain & diminished vision of left eye since 2 1/2 years. Slit lamp examination revealed a worm piercing iris muscle. The worm was removed by paracentesis of anterior chamber and sent to the Department of Microbiology. It was identified to be Gnathostoma spinigerum basing on the typical morphology of its cephalic end. The patient responded completely to oral albendazole therapy.